Numerical study of a concrete core temperature control building for tropics - Bharath Seshadri (2016)
Due to the hot and humid weather conditions in Singapore, air conditioning is widely used in buildings. In most cases, the air conditioning system consumes up to 50% of the total electricity consumption. One of the biggest challenges in achieving energy efficiency in buildings is to achieve a good indoor comfort level, while reducing the amount of energy consumed by air conditioning. One possible solution is radiant cooling systems; a high temperature cooling system that transports cooling energy to the building space through water, which is a more efficient heat transfer agent compared to air. In this research study, we investigate the performance of a specific type of radiant cooling system - Concrete Core Temperature Control (CCTC) using a transient building and energy modelling tool, CCTC is the practice of pumping cooling water through polymer pipes that are embedded in concrete of the building mass. The CCTC system makes use of the concrete mass as a heat sink for the internal heat Ioad in the building, hence cooling the building space. CCTC, which originated in Europe and is popular in temperate climates around the world, is yet to be validated and implemented in buildings in the tropics. A transient model of a typical commercial space in Singapore containing the CCTC system was developed and its performance measured under variable conditions. The performance of the CCTC was measured in terms of indoor occupant comfort and annual energy consumption. The results were compared to a conventional cooling and ventilation system. Annual weather data of Singapore and heat Ioad of a typical office were created to simulate the hypothetical building with and without CCTC using Transient System Simulation (TRNSYS) software. Variable conditions such as flow rate of the cooling water, mass of concrete and different floor zones in building were considered during the simulation exercise. It was found that, while achieving the same indoor comfort level, the building with the CCTC system was able to achieve significant energy savings at the chiller plant and air-distribution levels. The relative energy saving at chiller plant and air distribution is about 20% and 30%, respectively. On an annual basis, the building with CCTC consumed Iess energy overall when compared to the building without. Further to this, the a parametric analysis of CCTC design perimeters: mass flow rate of the chilled water and thermal mass containing the embedded pipes, was done.